The reality and prospects of tourism investment in Algeria and ways to develop it - Cheriet, Hocine elamine (Journal of Excellence for Economics and Management Research, 2020)
Tourism has become an industry of the 21st century, as it constitutes one of the concerns of the majority of the people of the world today, and Algeria, despite its possession of all the ingredients of tourism and qualifications that encourage tourism investment, which would make Algeria a tourist pole, but we find that tourism in our country has not been exploited in the right way, as a sector Tourism in Algeria is still facing many difficulties that prevent it so far from keeping pace with other strategic economic sectors and thus reaching the required level that is commensurate with its real potential, so this study came to uncover the most important obstacles to tourism investment J in Algeria and ways to address it.